The curing mechanism of epoxy resins - Fisch, W.; Hofmann, W.; Koskikallio, J.
A study has been made of the curing of epoxy resins from 2: 2-bis-(4-hydroxyphenyl)propane with phthialic anhydride. It is shown that in all cases an equilibrium is set up in which, after complete reaction of the epoxy groups, there are present anhydride, monoester and hydroxyl groups. The effect of temperature on the content of these groups has been determined and shown to be considerable. On heating cured resins, most of the monoester groups are split off and phthalic anhydride is evolved. A minimum point is obtained in the graph relating loss of weight and amount of anhydride used. The reason for this is discussed. The distribution of the various types of group has been determined in cured resins by chemical methods, which affords a good picture of the structure of resins cured under different conditions.
Keywords: EPOXY RESINS